2022
DOI: 10.26650/eor.2022911925
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and dentoalveolar dimensions in unilateral impacted canınes, a cone beam computed tomography study

Abstract: Purpose: To compare skeletal and dentoalveolar measurements of subjects with unilateral impacted canine versus the non-impacted contralateral side using cone beam computed tomography (CBCT). Materials and methods: 30 CBCTs with unilaterally impacted maxillary canines (Buccal=15, Palatal=15) were selected. Skeletal and dentoalveolar variables (alveolar ridge height of incisors, dentoalveolar height, angulations of incisors and canines, basal lateral width and premolar wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The BLW was studied in two split-mouth design studies [ 16 , 17 ]. In both cases, BLW was measured as the distance between the anterior nasal spine and the outermost dentoalveolar rim on the side of the impacted canine and the side without impaction.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The BLW was studied in two split-mouth design studies [ 16 , 17 ]. In both cases, BLW was measured as the distance between the anterior nasal spine and the outermost dentoalveolar rim on the side of the impacted canine and the side without impaction.…”
Section: Resultsmentioning
confidence: 99%
“…The mean BLW on the impacted side ranged from 19 ± 2.55 mm to 30.9 ± 1.41 mm and on the non-impacted side from 19.7 ± 2.29 mm to 27.5 ± 1.7 mm. Only one study reported a statistically significant outcome [ 16 ]. The meta-analysis showed a non-significant difference in the BLW between impacted and non-impacted sides ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations